Gender Disparities in Workplace Violence Among Italian Healthcare Workers: A Cross-Sectional Study - Stufano, Angela; De Maria, Luigi; Delvecchio, Giuseppe; Sifanno, Gianfranco; Maffione, Gianluca; Giannelli, Gianmarco; Schino, Valentina; Ravallese, Riccardo; Caputi, Antonio; Sivo, Donato; Lovreglio, Piero; Vimercati, Luigi (La Medicina del Lavoro, 2025)
Background: Workplace violence (WPV) is a prevalent issue globally among Healthcare Workers (HCWs). Moreover, WPV may disproportionately impact marginalized groups within the healthcare workforce, such as women and gender minorities. This study aims to examine the prevalence of WPV experienced by HCWs through a gender-focused lens and to investigate factors influencing the risk of WPV. Methods: A cross-sectional observational study was conducted over a month in Apulia, Italy, involving employees from major healthcare institutions, including hospitals, Local Health Authorities, selected correctional facilities, and Residences for Execution of Security Measures. The study used the Italian-validated WHO Workplace Violence in the Health Sector questionnaire, modified to include ’Other’ in the gender definition. Results: 3,259 HCWs participated, representing 88.8% of the 3,670 invited participants. The prevalence of violence incidents within the last 12 months was 29.6% in the HAW group and 57.1% in the CRW group. Within the HAW group, transgender and gender expansive (TGE) workers exhibited a higher prevalence of verbal, physical, and sexual harassment. Logistic regression analysis identified gender, job type, night shifts, interactions with specific patients, and the type of medical settings as significant predictors of experiencing various kinds of violence. Conclusions: The study underscores the vulnerability of TGE and female HCWs to workplace violence. These findings underscore the imperative for comprehensive yet gender-sensitive interventions promoting safety, equity, and inclusion in the healthcare workplace.